Molding sheets and molded bodies

The moldable sheet with a nonwoven fabric and resin layer addresses durability and versatility issues by enhancing resistance to damage and adding functional properties, facilitating diverse applications.

JP7616878B2Active Publication Date: 2025-01-17TOYOBO MC CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020207958
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-15
Publication Date
2025-01-17
Estimated Expiration
2040-12-15

AI Technical Summary

Technical Problem

Existing moldable sheets, such as spunbond nonwoven fabrics, are limited in their applications due to issues with durability and versatility, particularly when used for thermoforming processes.

Method used

A moldable sheet comprising a nonwoven fabric with specific fiber birefringence and a resin layer with controlled impregnation, featuring a molecular weight range and glass transition temperature, along with optional metal fillers and crosslinking agents, to enhance durability and versatility.

Benefits of technology

The sheet provides improved resistance to damage during molding, enabling various applications with properties like moisture resistance, electromagnetic shielding, and sound absorption, while maintaining ease of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616878000003
    Figure 0007616878000003
  • Figure 0007616878000004
    Figure 0007616878000004
  • Figure 0007616878000005
    Figure 0007616878000005
Patent Text Reader

Abstract

To provide a sheet for molding that is suitable for various uses.SOLUTION: A sheet for molding includes a nonwoven fabric 1 and a resin layer 2 laminated on the nonwoven fabric. The nonwoven fabric includes a fiber with a birefringence Δn of 0.005 or more and 0.050 or less. The resin layer includes an impregnation part 3 and a non-impregnation part 4. The impregnation part 3 includes a resin A with a number average molecular weight of 5,000 or more and 150,000 or less and a glass transition temperature (Tg) of 35°C or lower, the nonwoven fabric being impregnated with the impregnation part 3, while the nonwoven fabric not being impregnated with the non-impregnation part 4.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molding sheet having a resin layer, and a molded body. [Background technology]

[0002] Conventionally, various molding sheets are known. For example, Patent Document 1 discloses a spunbond nonwoven fabric suitable for thermoforming applications, which contains polyethylene terephthalate and a thermoplastic polystyrene copolymer. Furthermore, Patent Document 2 discloses a spunbond nonwoven fabric suitable for thermoforming applications, which has a shrinkage rate of 5% or less in the elongation direction length after elongation and leaving it in a 20°C atmosphere for 30 minutes, relative to the elongation direction length when elongated by 150% in a 130°C atmosphere. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-222950 A [Patent Document 2] JP 2017-222951 A Summary of the Invention [Problem to be solved by the invention]

[0004] Patent Documents 1 and 2 describe that spunbond nonwoven fabrics suitable for thermoforming are used as coffee filter materials, etc. In recent years, there has been an increasing demand for the application of molding sheets to various other uses.

[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a molding sheet that can be easily used for various applications. [Means for solving the problem]

[0006] The molding sheet according to the present invention comprises [1] a nonwoven fabric and a resin layer laminated on the nonwoven fabric, the nonwoven fabric containing fibers with a birefringence Δn of 0.005 or more and 0.050 or less, the resin layer containing resin A with a number average molecular weight of 5,000 or more and 150,000 or less and a glass transition temperature (Tg) of 35° C. or less, and the nonwoven fabric is impregnated with an impregnated portion and the nonwoven fabric is not impregnated with an unimpregnated portion. With this configuration, a molding sheet that is easy to use for various applications can be provided.

[0007] A preferred embodiment of the molding sheet is as follows: [2] to [8]. [2] The molding sheet according to [1], wherein the resin layer contains a metal filler. [3] The molding sheet according to [1] or [2], wherein the resin A is at least one selected from the group consisting of polyester resins, polyester urethane resins, polyamide resins, polyamide-imide resins, phenoxy resins, olefin resins, and acrylic resins. [4] The molding sheet according to any one of [1] to [3], wherein the resin layer contains a crosslinking agent. [5] The molding sheet according to any one of [1] to [4], wherein the fibers contain a resin B having an intrinsic viscosity of 0.3 dl / g or more and 0.9 dl / g or less. [6] The molding sheet according to [5], wherein the fibers contain a high Tg organic compound having a glass transition temperature higher than that of the resin B. [7] The molding sheet according to any one of [1] to [6], wherein the average thickness of the non-impregnated parts is smaller than the average thickness of the nonwoven fabric. [8] The molding sheet according to any one of [1] to [7], wherein the average thickness of the non-impregnated portions is greater than the average thickness of the impregnated portions.

[0008] The present invention also includes a molded body obtained by molding the molding sheet. A preferred embodiment of the molded body is as described in [9] below. [9] A molded body obtained by molding any one of the molding sheets [1] to [8]. Effect of the Invention

[0009] According to the present invention, the above-mentioned configuration makes it possible to provide a molding sheet that can be easily used for various applications. Moreover, by molding using the molding sheet, various molded products can be obtained. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view of a molding sheet according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a photograph, enlarged 100 times, showing a part of the surface of the resin layer of the molding sheet of Example 1. As shown in FIG. [Diagram 3] FIG. 3 is a photograph, used as a substitute for a drawing, of a molding sheet in which a tear was confirmed when a part of the surface of the resin layer of the molding sheet was photographed at 100 times magnification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in more detail below based on the following embodiment, but the present invention is not limited to the following embodiment, and can be modified as appropriate within the scope of the above and below, and all of these are included in the technical scope of the present invention. Note that the dimensions of various members in the drawings may differ from the actual dimensions, as priority is given to helping understand the features of the present invention.

[0012] The molding sheet according to the embodiment comprises a nonwoven fabric and a resin layer laminated to the nonwoven fabric, the nonwoven fabric containing fibers having a birefringence Δn of 0.005 or more and 0.050 or less, the resin layer containing resin A having a number average molecular weight of 5,000 or more and 150,000 or less and a glass transition temperature (Tg) of 35°C or less, and the nonwoven fabric has an impregnated portion and a non-impregnated portion that is not impregnated in the nonwoven fabric.

[0013] The present inventors have found that the above-mentioned configuration makes it easier to prevent damage to the nonwoven fabric and resin layer of the molding sheet during molding. The molded body molded using the molding sheet having the above-mentioned configuration has a resin layer, and thus exhibits various properties such as moisture resistance, waterproofness, and durability depending on the properties of the resin. In addition, if a filler having properties such as electromagnetic wave shielding and sound absorption is contained in the resin layer, these properties can be imparted to the molded body. In this way, the molding sheet having the above-mentioned configuration can be easily used for various purposes. Below, the molding sheet according to the embodiment will be described with reference to FIG. 1. FIG. 1 is a cross-sectional view of the molding sheet according to the embodiment.

[0014] 1, a molding sheet 10 according to an embodiment includes a nonwoven fabric 1 and a resin layer 2 laminated on the nonwoven fabric 1. In detail, the resin layer 2 is laminated on the nonwoven fabric 1 in a state in which the resin layer 2 is partially impregnated into the nonwoven fabric 1. That is, the resin layer 2 includes an impregnated portion 3 that has impregnated into the nonwoven fabric 1. Since the resin layer 2 includes the impregnated portion 3, the resin layer 2 is less likely to peel off from the nonwoven fabric 1.

[0015] The average thickness of the impregnated portion 3 is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 12 μm or more. This makes it difficult for the resin layer 2 to peel off during molding. On the other hand, the upper limit of the average thickness of the impregnated portion 3 is not particularly limited, but may be, for example, 100 μm or less, 80 μm or less, 70 μm or less, 40 μm or less, or 25 μm or less.

[0016] Furthermore, the resin layer 2 has a non-impregnated portion 4 that is not impregnated into the nonwoven fabric 1. By having the non-impregnated portion 4, the resin layer 2 becomes less likely to be damaged during molding.

[0017] The average thickness of the non-impregnated portion 4 is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and even more preferably 20 μm or more. This makes it difficult for the resin layer 2 to be damaged during molding. On the other hand, the average thickness of the non-impregnated portion 4 is preferably 130 μm or less, more preferably 80 μm or less, even more preferably 75 μm or less, and even more preferably 70 μm or less. This makes it possible to reduce the surface roughness of the non-impregnated portion 4.

[0018] The average thickness of the non-impregnated parts 4 is preferably smaller than the average thickness of the nonwoven fabric 1, and more preferably equal to or less than 1 / 2 the average thickness of the nonwoven fabric 1. This reduces bias in stress during elongation of the resin layer 2, making it less likely to break. The average thickness of the non-impregnated parts 4 may be equal to or more than 1 / 50 of the average thickness of the nonwoven fabric 1.

[0019] The average thickness of the non-impregnated parts 4 is preferably larger than the average thickness of the impregnated parts 3, more preferably 1.2 times or more the average thickness of the impregnated parts 3, and even more preferably 1.3 times or more the average thickness of the impregnated parts 3. This makes it possible to reduce the surface roughness of the non-impregnated parts 4. Furthermore, the average thickness of the non-impregnated parts 4 is preferably 6 times or less the average thickness of the impregnated parts 3, more preferably 5 times or less, and even more preferably 4 times or less. This makes it difficult for the resin layer 2 to be damaged during molding.

[0020] The average thickness of the non-impregnated portion 4 can be measured, for example, by the following method. First, three points are selected and marked in a 10 mm square area on the surface 4s of the non-impregnated portion 4 of the forming sheet 10, and the forming sheet 10 is frozen with liquid nitrogen. Next, the forming sheet 10 is cut in the thickness direction T so that each point can be observed. After that, each cross section is observed at 2x magnification with a stereomicroscope, and in the image, a straight line is drawn in the thickness direction T from one of the three points (point A) on the surface 4s of the non-impregnated portion 4. The distance (μm) between the intersection (point B) of the above line and the surface 1s of the nonwoven fabric 1 and point A is measured, and the average value is taken as the average thickness (μm) of the non-impregnated portion 4.

[0021] The average thickness of the impregnated portion 3 may be determined, for example, by measuring the distance (μm) between the intersection (point C) of the straight line in the thickness direction T and the impregnated surface 3s of the impregnated portion 3 and the point B on the surface 1s of the nonwoven fabric 1 in the images of each cross section, and averaging the distances to obtain the average thickness (μm) of the impregnated portion 3. In this case, the impregnated surface 3s means the surface of the impregnated portion 3 opposite to the surface 1s of the nonwoven fabric 1.

[0022] In FIG. 1, the nonwoven fabric 1 has the resin layer 2 on one side, but the nonwoven fabric 1 may have the resin layer 2 on both sides. It is preferable that the resin layer 2 is provided on one side of the nonwoven fabric 1, since this allows for weight reduction. It is also preferable that no other layer is formed on the surface 4s of the non-impregnated portion 4, and the surface 4s is exposed. This makes it easier to improve processability.

[0023] The nonwoven fabric 1 contains fibers having a birefringence Δn of 0.005 or more and 0.050 or less. When the birefringence (Δn) of the fibers is 0.005 or more, the rigidity of the nonwoven fabric 1 is improved, and the shape retention of the molded body can be easily improved. The birefringence (Δn) is preferably 0.007 or more, more preferably 0.008 or more. On the other hand, when the birefringence (Δn) is 0.050 or less, the processability can be easily improved. The birefringence (Δn) is preferably 0.040 or less, more preferably 0.020 or less. The birefringence (Δn) can be specifically measured by the method described in the Examples below.

[0024] In 100% by mass of the nonwoven fabric, the content of fibers having a birefringence Δn of 0.005 or more and 0.050 or less is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, still more preferably 95% by mass or more, particularly preferably 98% by mass or more, and most preferably 100% by mass.

[0025] The fibers contained in the nonwoven fabric 1 are preferably polyester fibers, polyamide fibers, and polyolefin fibers, more preferably polyester fibers, and even more preferably thermoplastic polyester fibers. These may be used alone or in combination of two or more kinds.

[0026] Examples of polyester fibers include those containing polyethylene terephthalate as a main component. Polyethylene terephthalate is excellent in mechanical strength, heat resistance, shape retention, and the like. In order to effectively exert such effects, the content of polyethylene terephthalate in the polyester fiber is preferably 90% by mass or more, more preferably 93% by mass or more, and even more preferably 94% by mass or more, when the polyester fiber is taken as 100% by mass. On the other hand, the content of polyethylene terephthalate is preferably 99.8% by mass or less, taking into consideration the content of high Tg organic compounds described below. The polyester fiber may contain polyesters other than polyethylene terephthalate, such as polytrimethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. The description of the content can be referred to when polyamide, polyolefin, or the like is used as the material of the fiber.

[0027] The fibers contained in the nonwoven fabric 1 preferably contain a resin B having an intrinsic viscosity of 0.3 dl / g or more and 0.9 dl / g or less. The fibers preferably contain a high Tg organic compound having a higher glass transition temperature than that of the resin B. The resin B is preferably a thermoplastic resin. Examples of the resin B include polyester resin, polyamide resin, and polyolefin resin.

[0028] The content of resin B is preferably 92% by mass or more, more preferably 93% by mass or more, and even more preferably 94% by mass or more, when the fibers contained in the woven fabric 1 are taken as 100% by mass. On the other hand, the content of resin B is preferably 99.8% by mass or less, and more preferably 99.5% by mass or less, taking into account the content of the high Tg organic compound.

[0029] The glass transition temperature of resin B is preferably 120°C or less, more preferably 100°C or less, and even more preferably 90°C or less. This makes it easier for the high Tg organic compound to exert its effect. On the other hand, the glass transition temperature of resin B may be 25°C or more, 35°C or more, or 50°C or more. The glass transition temperature can be measured at a temperature rise rate of 20°C / min according to JIS K7122 (1987). The glass transition temperature is preferably the midpoint glass transition temperature, which is the temperature at the point where a straight line equidistant in the vertical axis direction from the straight line extending each baseline in the DSC curve intersects with the curve of the stepwise change part of the glass transition.

[0030] The intrinsic viscosity is preferably 0.3 dl / g or more and 0.9 dl / g or less. By making the intrinsic viscosity 0.3 dl / g or more, the nonwoven fabric 1 is less susceptible to thermal degradation and the durability thereof can be improved. Therefore, the intrinsic viscosity is more preferably 0.4 dl / g or more, even more preferably 0.5 dl / g or more, and even more preferably 0.55 dl / g or more. On the other hand, if the intrinsic viscosity is 0.9 dl / g or less, the stress during thermoforming of the nonwoven fabric 1 can be easily reduced. Therefore, the intrinsic viscosity is more preferably 0.7 dl / g or less. The intrinsic viscosity can be determined, for example, by weighing 0.1 g of the resin, dissolving it in 25 ml of a mixed solvent of phenol / tetrachloroethane (60 / 40 (weight ratio)), measuring the viscosity three times at 30° C. using an Ostwald viscometer, and calculating the average value.

[0031] Examples of high Tg organic compounds include polystyrene, polystyrene copolymers, polycarbonate, and polyacrylonitrile. Among these, polystyrene copolymers are preferred. The high Tg organic compound is preferably a thermoplastic organic compound. The glass transition temperature of the high Tg organic compound is preferably 100°C or higher and 160°C or lower. The high Tg organic compound is more preferably incompatible with the resin B. Since the high Tg organic compound has a higher glass transition temperature than the resin B, the high Tg organic compound solidifies first during cooling of the melt spinning, inhibiting orientation and disrupting crystallinity. As a result, the breaking elongation of the obtained nonwoven fabric 1 can be improved and the stress during elongation can be further reduced. For this reason, the glass transition temperature of the high Tg organic compound is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher. On the other hand, the glass transition temperature is preferably 160°C or lower, more preferably 150°C or lower, in consideration of spinning productivity. The glass transition temperature can be determined by measuring at a temperature increase rate of 20° C. / min in accordance with JIS K7122 (1987). The glass transition temperature is preferably the midpoint glass transition temperature, which is the temperature at the point where a line equidistant in the vertical direction from the line extending each baseline in the DSC curve intersects with the curve of the stepwise change in the glass transition.

[0032] As the polystyrene copolymer, for example, at least one selected from the group consisting of styrene-conjugated diene block copolymer, acrylonitrile-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, styrene-acrylic acid ester copolymer, and styrene-methacrylic acid ester copolymer is preferable. Among these, at least one selected from the group consisting of styrene-acrylic acid ester copolymer and styrene-methacrylic acid ester copolymer is more preferable, and styrene-methacrylic acid ester copolymer is even more preferable. As the styrene-methacrylic acid ester copolymer, for example, styrene-methyl methacrylate-maleic anhydride copolymer can be mentioned. These may be contained alone or in combination. As a commercially available product, PLEXIGLAS HW from Rohm GmbH & Co. KG is 55, which can exert an excellent effect even with a small amount added.

[0033] The content of the high Tg organic compound in the fibers contained in the nonwoven fabric 1 is preferably 0.02% by mass or more and 8% by mass or less, when the fibers are taken as 100% by mass. By making it 0.02% by mass or more, the effect of the addition can be easily obtained. For this reason, the content of the high Tg organic compound is more preferably 0.05% by mass or more, and even more preferably 0.2% by mass or more. On the other hand, by making the content of the high Tg organic compound 8% by mass or less, the difference in extensibility between the resin B and the high Tg organic compound can be reduced, making it difficult for the fibers to break. For this reason, the content of the high Tg organic compound is more preferably 8% by mass or less, even more preferably 7% by mass or less, and even more preferably 6% by mass or less.

[0034] The fiber diameter of the fibers contained in the nonwoven fabric 1 is preferably 5 μm or more. By making the fiber diameter 5 μm or more, the shape retention of the molded body can be improved. For this reason, the fiber diameter is preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 12 μm or more. On the other hand, the upper limit of the fiber diameter is not particularly limited, and may be, for example, 80 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 35 μm or less. Specifically, the fiber diameter can be measured by the method described in the Examples below.

[0035] It is preferable that the fibers of the nonwoven fabric 1 are not entangled. This makes the nonwoven fabric 1 easier to mold. In addition, the fibers contained in the nonwoven fabric 1 are preferably long fibers. By using long fibers, the force applied during molding is uniformly distributed, making it easier to prevent stress concentration and improve the shape retention of the molded body. For this reason, the nonwoven fabric is preferably a spunbonded nonwoven fabric or a meltblown nonwoven fabric, and more preferably a spunbonded nonwoven fabric.

[0036] The basis weight of the nonwoven fabric may be adjusted taking into consideration the rigidity after molding, and is not particularly limited. 2 More than 500g / m 2It is preferable that the basis weight is 20 g / m or less. 2 If the weight is more than this, the fabric will be less likely to break during molding. Therefore, the weight is more preferably 80 g / m 2 More preferably, 150 g / m 2 On the other hand, the basis weight is 500g / m 2 If it is less than this, it will be easy to stretch during molding. Therefore, the basis weight is more preferably 400 g / m 2 More preferably, 300 g / m or less 2 The basis weight of the nonwoven fabric can be specifically measured by the method described in the Examples below.

[0037] The average thickness of the nonwoven fabric is preferably 100 μm or more and 3000 μm or less. If the thickness is 100 μm or more, the fabric is less likely to break during molding. Therefore, the thickness is more preferably 200 μm or more, and even more preferably 400 μm or more. On the other hand, if the thickness is 3000 μm or less, the fabric is more likely to stretch during molding. Therefore, the thickness is more preferably 2000 μm or less, and even more preferably 1000 μm or less. The average thickness of the nonwoven fabric can be specifically measured by the method described in the Examples below.

[0038] The nonwoven fabric 1 preferably has a breaking elongation of 200% or more after heating at 130°C for 1 minute. This allows the nonwoven fabric 1 to be easily adapted to molding processes such as deep drawing. More preferably, the breaking elongation is 250% or more, even more preferably, 260% or more, even more preferably, 280% or more, and particularly preferably, 300% or more. On the other hand, the upper limit of the breaking elongation may be approximately 500% or less, or may be 450% or less. The above-mentioned elongation is expressed as a percentage of the elongation relative to the initial length, that is, it can be calculated by {(length after elongation-initial length) / initial length}×100. For example, when a 100 mm long piece is elongated to 250 mm, the elongation is 150%.

[0039] Nonwoven fabric 1 has a basis weight of 200 g / m2 at 20% elongation stress after heating at 130°C for 1 minute. 2It is preferably 40N / 5cm or less in terms of conversion. This can improve mold-following ability during thermoforming. More preferably, it is 39N / 5cm or less, even more preferably 38N / 5cm or less, even more preferably 37N / 5cm or less, and particularly preferably 36N / 5cm or less. On the other hand, the lower limit is not particularly limited, but considering the suppression of wrinkles after molding, it is preferably 20N / 5cm or less. Note that 20% elongation means, for example, when the initial length is 100mm, it is elongated to a length of 120mm.

[0040] The breaking elongation and stress at 20% elongation of the nonwoven fabric 1 can be measured, for example, by the following method. First, five sample pieces each having a width of 5 cm and a length of 20 cm are cut out from the nonwoven fabric 1 in the longitudinal and transverse directions. Next, the sample is set with a chuck distance of 5 cm and placed in a furnace heated to 130° C. After one minute has elapsed, the sample is deformed in the furnace at a tensile speed of 10 cm / min using a universal tensile tester manufactured by Orientec Co., Ltd. to obtain a strain-stress curve. From the strain-stress curve, the breaking elongation and stress at 20% elongation are read, and the average values ​​of five points in each of the longitudinal and transverse directions are taken as the breaking elongation and stress at 20% elongation.

[0041] When manufacturing the nonwoven fabric 1, the manufacturing methods described in JP 2017-222950 A and JP 2017-222951 A can be referred to.

[0042] The resin layer 2 laminated on the nonwoven fabric 1 contains a resin A having a number average molecular weight of 5,000 or more and 150,000 or less, and a glass transition temperature (Tg) of 35° C. or less.

[0043] By having the number average molecular weight of resin A be 5,000 or more, the toughness of the resin layer 2 is easily improved, and the resin is easily able to follow deformation during molding. The number average molecular weight is preferably 10,000 or more, more preferably 20,000 or more. On the other hand, by having the number average molecular weight be 150,000 or less, when mixing the resin with a solvent and applying it to the nonwoven fabric 1 to form the resin layer 2, the viscosity of the solution can be easily reduced, making it easier to apply. Even when the resin layer 2 is formed by heating and melting the resin to adhere to the nonwoven fabric 1, the viscosity of the resin in the molten state can be easily reduced, making it easier for the resin to penetrate into the nonwoven fabric 1. As a result, the adhesive strength of the resin layer 2 to the nonwoven fabric 1 is improved, and the resin layer 2 is less likely to peel off during molding. The number average molecular weight can be determined in terms of polystyrene using, for example, a gel permeation chromatography (GPC) device.

[0044] The glass transition temperature (Tg) of resin A is 35°C or less, so that the resin can easily follow deformation during molding. The glass transition temperature (Tg) of resin A is preferably 25°C or less, more preferably 10°C or less, even more preferably -5°C or less, and even more preferably -10°C or less. On the other hand, the glass transition temperature (Tg) of resin A may be -130°C or more, -50°C or more, or -30°C or more. The glass transition temperature is measured at a heating rate of 20°C / min according to JIS K7122 (1987). The glass transition temperature is preferably the midpoint glass transition temperature, which is the temperature at the point where a straight line equidistant in the vertical axis direction from the straight line extending each baseline in the DSC curve intersects with the curve of the stepwise change part of the glass transition.

[0045] In 100% by mass of the resin layer, the content of resin A is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more.

[0046] Resin A is preferably a thermoplastic resin, more preferably an amorphous thermoplastic resin, which makes it easier to heat mold the molding sheet 10. Specifically, resin A is preferably at least one selected from the group consisting of polyester resin, polyester urethane resin, polyamide resin, polyamideimide resin, phenoxy resin, olefin resin, and acrylic resin, more preferably at least one selected from the group consisting of polyester resin and olefin resin, and even more preferably polyester resin.

[0047] The polyester resin is formed mainly by reacting a carboxylic acid component with a hydroxyl group component. Examples of the carboxylic acid component include terephthalic acid, isophthalic acid, adipic acid, azelaic acid, sebacic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, dimer acid, hydrogenated dimer acid, and naphthalenedicarboxylic acid. These may be used alone or in combination of two or more. Examples of the hydroxyl group component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, dipropylene glycol, diethylene glycol, neopentyl glycol, 2,2,4-trimethyl-1,3-pentanediol, tricyclodecane dimethanol, neopentyl glycol hydroxypivalic acid ester, 1,9-nonanediol, 2-methyloctanediol, 1,10-dodecanediol, 2-butyl-2-ethyl-1,3-propanediol, polytetramethylene glycol, polyoxymethylene glycol, cyclohexane dimethanol, etc. These may be used alone or in combination of two or more.

[0048] Examples of polyester urethane resins include those obtained by addition polymerization of polyester polyols and polyisocyanates. Examples of polyester polyols include those obtained by condensation reaction of polybasic acids such as dipic acid, azelaic acid, sebacic acid, terephthalic acid, isophthalic acid, phthalic acid, and succinic acid with polyhydric alcohols such as propylene glycol, ethylene glycol, tetramethylene glycol, butanediol, hexanediol, and neopentyl glycol. Examples of polyisocyanates include aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate (MDI), tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), etc.; aliphatic diisocyanates such as hexamethylene diisocyanate (HDI), lysine methyl ester diisocyanate (LDI), etc.; alicyclic diisocyanates such as dicyclohexylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), etc. These may be used alone or in combination of two or more.

[0049] Polyamide resins are polymers having amide bonds in the molecule. Examples of polyamide resins include nylon 6,6, nylon 6,9, nylon 6,10, nylon 6,12, nylon 6, nylon 12, nylon 11, nylon 4,6, etc. These may be used alone or in combination of two or more.

[0050] A polyamide-imide resin is a polymer having an amide bond and an imide bond, and examples of the polyamide-imide resin include those obtained by reacting an acid component with a diamine.

[0051] Examples of the acid component include trimellitic acid, its anhydrides, and chlorides; tetracarboxylic acids such as pyromellitic acid, biphenyl tetracarboxylic acid, biphenyl sulfone tetracarboxylic acid, benzophenone tetracarboxylic acid, biphenyl ether tetracarboxylic acid, ethylene glycol bistrimellitate, and propylene glycol bistrimellitate, and their anhydrides; aliphatic dicarboxylic acids such as oxalic acid, adipic acid, malonic acid, sebacic acid, azelaic acid, dodecane dicarboxylic acid, dicarboxy polybutadiene, dicarboxy poly (acrylonitrile-butadiene), and dicarboxy poly (styrene-butadiene); alicyclic dicarboxylic acids such as 1,4-cyclohexane dicarboxylic acid, 1,3 cyclohexane dicarboxylic acid, 4,4'-dicyclohexylmethane dicarboxylic acid, and dimer acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, diphenyl sulfone dicarboxylic acid, diphenyl ether dicarboxylic acid, and naphthalene dicarboxylic acid; and the like. These may be used alone or in combination of two or more.

[0052] Examples of diamines include aliphatic diamines such as ethylenediamine, propylenediamine, and hexamethylenediamine, and diisocyanates thereof; alicyclic diamines such as 1,4-cyclohexanediamine, 1,3-cyclohexanediamine, isophoronediamine, and 4,4'-dicyclohexylmethanediamine, and diisocyanates thereof; aromatic diamines such as m-phenylenediamine, p-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylether, 4,4'-diaminodiphenylsulfone, benzidine, o-tolidine, 2,4-tolylenediamine, 2,6-tolylenediamine, and xylylenediamine, and diisocyanates thereof; etc. These may be used alone or in combination of two or more.

[0053] Examples of phenoxy resins include resins obtained by reacting epihalohydrin with a dihydric phenol compound, and resins obtained by reacting a divalent epoxy compound with a dihydric phenol compound.Specific examples include bisphenol-type phenoxy resins such as bisphenol A-type phenoxy resins, bisphenol F-type phenoxy resins, bisphenol S-type phenoxy resins, bisphenol M-type phenoxy resins, bisphenol P-type phenoxy resins, bisphenol Z-type phenoxy resins, and phenoxy resins having two or more bisphenol skeletons, novolac-type phenoxy resins, and naphthalene-type phenoxy resins.These may be used alone or in combination of two or more.

[0054] Examples of the olefin resin include homopolymers or copolymers of olefins such as ethylene, propylene, and butene; copolymers of these olefins with monomer components copolymerizable therewith; and maleic anhydride modified versions of these. Examples of the olefin resin include at least one selected from the group consisting of polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-α-olefin copolymer, ethylene-propylene copolymer, ethylene-butene copolymer, and propylene-butene copolymer.

[0055] Examples of acrylic resins include those obtained by polymerizing or copolymerizing (meth)acrylic monomers such as (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, (meth)acrylamide, (meth)acrylonitrile, and glycidyl (meth)acrylate. These may be used alone or in combination of two or more.

[0056] Resin A may have a reactive functional group capable of reacting with a crosslinking agent described later. Examples of the reactive functional group include a carboxyl group, a hydroxyl group, a methylol group, and an amide group. Resin A is preferably present in a form crosslinked by a crosslinking agent.

[0057] The resin layer 2 preferably contains a metal filler. Examples of the metal filler include a metal filler of a simple metal such as aluminum, zinc, iron, silver, or copper, a metal filler of a metal oxide such as zinc oxide, or a metal filler of an alloy such as a Ni-Fe alloy or a Si-Al-Fe alloy. The metal filler may or may not have magnetism, but is preferably magnetic. These may be used alone or in combination of two or more.

[0058] The content of the metal filler is preferably 2 parts by mass or more, more preferably 5 parts by mass or more, and preferably 200 parts by mass or less, more preferably 100 parts by mass or less, even more preferably 50 parts by mass or less, and particularly preferably 40 parts by mass or less, relative to 100 parts by mass of resin A.

[0059] The resin layer 2 preferably contains a crosslinking agent. Examples of the crosslinking agent include isocyanate-based crosslinking agents, melamine-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, epoxy-based crosslinking agents, polyamide-based crosslinking agents, and carbodiimide-based crosslinking agents. Among these, isocyanate-based crosslinking agents are preferable. Examples of the isocyanate-based crosslinking agent include compounds having two or more isocyanate groups in one molecule. For example, diisocyanate compounds such as tolylene diisocyanate, hexamethylene diisocyanate, and 4,4'-diphenylmethane diisocyanate, biuret-type polyisocyanate compounds such as BI-7960 manufactured by Baxenden Co., Ltd., polyisocyanate compounds having an isocyanurate ring such as Coronate HX manufactured by Tosoh Co., Ltd., and adduct-type polyisocyanate compounds such as Coronate HL, which is a trimethylolpropane adduct-type trimer manufactured by Tosoh Co., Ltd., and the like. The isocyanate crosslinking agent may be a blocked isocyanate in which an isocyanate group in the compound is inactivated with a blocking agent such as DMP (dimethylpyrazole).

[0060] The content of the crosslinking agent is preferably 2 parts by mass or more, more preferably 4 parts by mass or more, and preferably 20 parts by mass or less, more preferably 14 parts by mass or less, relative to 100 parts by mass of resin A. The crosslinking agent may be contained in resin layer 2 in a form capable of reacting with the reactive functional group of resin A, or may be contained in resin layer 2 in a form having reacted with the reactive functional group.

[0061] The resin layer 2 may also contain flame retardants such as antimony oxide, aluminum hydroxide, magnesium hydroxide, etc., plasticizers such as phthalates, adipates, etc., hydrolysis inhibitors such as carbodiimides, etc., sound absorbing fillers such as silica, etc. These additives may be used alone or in combination of two or more.

[0062] It is preferable that the molding sheet 10 does not have any damaged parts in the resin layer 2 and the nonwoven fabric 1 after the following molding process in accordance with JIS 1096 (2010) 8.18.2B method. The following pressing amount is more preferably 17 mm, and even more preferably 20 mm. <Molding processing conditions> The molding sheet 10 is cut into a circle with a diameter of 72 mm. Next, a convex mold having a cylindrical portion with a diameter of 25 mm and a hemispherical portion with a radius of 12.5 mm provided at the tip of the cylindrical portion, and a concave mold capable of fitting into the hemispherical portion are prepared. Next, the molding sheet 10 is placed on the concave mold with the resin layer 2 side facing the concave mold, and a ring-shaped pressing plate is placed on the peripheral portion of the molding sheet 10. Next, it is heated under conditions of a heating temperature of 140°C and a heating time of 1 minute, and then the hemispherical portion and the cylindrical portion are pressed 13 mm vertically into the molding sheet 10 at a speed of 20 mm / min, and then the mold is released after maintaining the heating temperature for 30 seconds. Then, it is cooled with cold air from a dryer for 1 minute, and the molded body is taken out.

[0063] The molding sheet preferably has a peel strength of the resin layer 2 of 1.0 N / cm or more. This makes the resin layer 2 less likely to be damaged during molding. Therefore, the peel strength of the resin layer 2 is more preferably 2.0 N / cm or more, even more preferably 3.0 N / cm or more, and even more preferably 4.0 N / cm or more. On the other hand, the upper limit is not particularly limited, but may be, for example, 15 N / cm or less, or 10 N / cm or less. The peel strength of the resin layer 2 can be measured by the method described in the Examples below.

[0064] The resin layer 2 can be formed on the nonwoven fabric 1 by a transfer method, a screen printing method, or the like. In the transfer method, the resin may be heated and melted, or a solvent such as methyl ethyl ketone may be mixed with the resin. For example, when the transfer method is performed, a resin layer coating material is applied to a release paper or a release film at 300 to 600 g / cm. 2and drying at 120°C to 160°C for 2 to 4 minutes. In 100% by mass of the coating material for the resin layer, the solid content of the resin is preferably 20% by mass to 40% by mass. Thereafter, the resin layer with the release layer is laminated with the resin layer side facing the surface of the nonwoven fabric, and dried at 50 to 70°C and 15 to 25 N / cm 2 It is preferable to perform thermocompression bonding under the above conditions and leave the material for 24 to 72 hours at 50° C. to 70° C. This makes it easier to control the thicknesses of the impregnated portion 3 and the non-impregnated portion 4 within a preferred range.

[0065] The present invention also includes a molded body obtained by molding the molding sheet 10. In molding, the molding sheet 10 may be subjected to drawing such as shallow drawing or deep drawing under heating conditions of, for example, 100 to 180° C. The shape of the processing is not limited, and it is possible to perform cylindrical drawing, square tube drawing, conical drawing, pyramidal drawing, spherical head drawing, other irregular drawing, and the like. EXAMPLES

[0066] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be modified within the scope of the above and below mentioned aims, and all such modifications are included in the technical scope of the present invention.

[0067] Birefringence (Δn): Ten random points were selected from the nonwoven fabric, and single fibers were taken out. The fiber diameter and retardation were measured using a Nikon OPTIPHOT-POL polarizing microscope to determine the birefringence (Δn).

[0068] Fiber diameter: Five randomly selected points on the sample (long fiber fleece before temporary bonding) were used to measure the diameter of single fibers (n=20) using an optical microscope, and the average value was calculated.

[0069] Intrinsic viscosity: 0.1 g of resin B was weighed out and dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (60 / 40 (weight ratio)). The viscosity was measured three times at 30° C. using an Ostwald viscometer, and the average value was calculated.

[0070] Average thickness of nonwoven fabric: The average thickness of the nonwoven fabric was measured based on JIS L 1913 (2010) 6.1.

[0071] Nonwoven fabric basis weight: The nonwoven fabric basis weight was calculated based on "Mass per unit area" in JIS L 1913 (2010) 6.2.

[0072] Average thickness of non-impregnated part: Three points were selected and marked in a 10 mm square area on the surface of the non-impregnated part of the molding sheet, and the molding sheet was frozen with liquid nitrogen. Next, the molding sheet was cut in the thickness direction so that each point could be observed. After that, each cross section was observed at 2x magnification with a stereo microscope manufactured by LEICA, and in the image, a straight line was drawn in the thickness direction from one of the three points (point A) on the surface of the non-impregnated part. The distance (μm) between the intersection (point B) of the above line and the surface of the nonwoven fabric and point A was measured, and the average value was taken as the average thickness (μm) of the non-impregnated part.

[0073] Average thickness of the impregnated portion: In each of the cross-sectional images, the distance (μm) between the intersection (point C) of the straight line in the thickness direction and the impregnated surface of the impregnated portion and point B on the surface of the nonwoven fabric was measured, and the average value was taken as the average thickness (μm) of the impregnated portion.

[0074] Number average molecular weight of resin: A chromatogram was measured using a gel permeation chromatography (GPC) device manufactured by Shimadzu Corporation, and the number average molecular weight (Mn) of resin A was determined based on a calibration curve using standard polystyrene.

[0075] Peel strength: The molding sheet was cut to 100 mm length and 250 mm width. Then, a hot melt tape with a width of 20 mm and a thickness of 25 μm manufactured by Sun Chemical Industry Co., Ltd. was thermocompressed to the resin layer of the molding sheet with an iron heated to a surface temperature of 120° C. Then, using an autograph tensile tester manufactured by Shimadzu Corporation, the hot melt tape was peeled off together with the resin layer under the conditions of an autograph speed of 300 mm / min, a peel distance of 50 mm, and a peel angle of 180°, and the measurement was repeated twice to obtain the average value as the peel strength (N / cm).

[0076] Surface roughness: The arithmetic mean height (roughness Ra) of the surface on the resin layer side of the molding sheet was determined based on JIS B 0601 4.2.1.

[0077] Moldability evaluation: The moldability of the moldable sheet was evaluated by carrying out the following molding process in accordance with JIS 1096 (2010) 8.18.2B method. <Molding processing conditions> The molding sheet was cut into a circle with a diameter of 72 mm. Next, a convex mold having a cylindrical portion with a diameter of 25 mm and a hemispherical portion with a radius of 12.5 mm provided at the tip of the cylindrical portion, and a concave mold capable of fitting into the hemispherical portion were prepared. Next, the molding sheet was placed on the concave mold with the resin layer side facing the concave mold, and a ring-shaped pressing plate was placed on the peripheral portion of the molding sheet. Next, it was heated under conditions of a heating temperature of 140°C and a heating time of 1 minute, and then the hemispherical portion and the cylindrical portion were pressed 13 mm vertically against the molding sheet at a speed of 20 mm / min, and then released after maintaining for 30 seconds. After that, it was cooled with cold air from a dryer for 1 minute, and the molded body was taken out.

[0078] The surface of the molded body taken out was observed and evaluated as to whether it was a good, fair, or bad result. Similarly, molding was performed under conditions of being pressed 17 mm or 20 mm in the vertical direction, and the moldability of the molding sheet was evaluated. ×: At least one of the resin layer and the nonwoven fabric had a visually observable damaged portion. △There was no visible damage to the resin layer or nonwoven fabric, but damage was visible to the naked eye when observed at 100 times magnification using a scanning electron microscope in at least one of the resin layer and nonwoven fabric (see Figure 3). There was no visible damage to the resin layer or nonwoven fabric, and no visible damage when observed at 100x magnification using a scanning electron microscope.

[0079] FIG. 2 shows a photograph, enlarged 100 times, of a part of the surface of the resin layer of the molding sheet of Example 1 described later.

[0080] Example 1 Using a spunbond spinning facility, polyethylene terephthalate (hereinafter referred to as "PET") having an intrinsic viscosity of 0.63 dl / g and a glass transition temperature of 80°C was used as resin B. A styrene-methyl methacrylate-maleic anhydride copolymer (PLEXIGLAS HW55 (hereinafter referred to as "HW55") manufactured by Rohm GmbH & Co. KG) having a glass transition temperature of 122°C was mixed with PET at a ratio of 0.40 mass% to obtain a resin composition. The resin composition was spun from a spinneret with an orifice diameter of 0.23 mm at a single hole output rate of 0.75 g / min. Further, a 0.6 kg / cm2 gas was added to the ejector. 2 Dry air was supplied at a pressure (jet pressure) of 10 ...

[0081] The obtained long fiber fleece was pre-pressed using a pair of pre-heat pressing rolls consisting of two flat rolls, with the surface temperature of each roll set to 80°C and the pressing pressure set to 8 kN / m, and then the roll surface temperature was set to 145°C and the pressing pressure set to 3.0 kgf / cm. 2 The nonwoven fabric had a basis weight of 210 g / m. 2 , and the thickness was 650 μm.

[0082] Next, the following resin and solvent were mixed in the following ratio, heated to 30° C., and dissolved in a stirrer, and a crosslinking agent was added in the following ratio to obtain a coating material for the resin layer. Resin A: Vylon BX-1001 (manufactured by Toyobo Co., Ltd.) 100 parts Solvent: 200 parts methyl ethyl ketone Crosslinking agent: Blocked isocyanate 7960 (Baxenden) 8 parts

[0083] Furthermore, the paint for the resin layer was applied to a release film SP3000#75 (manufactured by Toyo Cross Co., Ltd.) at a rate of 450 g per square meter using a comma coater, and then dried for 3 minutes in a dryer at 150°C to obtain a resin layer with a release film.

[0084] Next, the resin layer side of the resin layer with release film is placed on the surface of the spunbond nonwoven fabric, and the fabric is laminated to the resin layer side of the spunbond nonwoven fabric at 60° C. and 20 N / cm 2 The resulting laminate with the release film was left for 48 hours in a room heated to 60°C to transfer the resin layer. The release film was then peeled off to obtain a molding sheet.

[0085] Example 2 A molding sheet was obtained in the same manner as in Example 1, except that Coronate HX (manufactured by Tosoh Corporation) was used as the crosslinking agent.

[0086] Example 3 A molding sheet was obtained in the same manner as in Example 1, except that Coronate HL (manufactured by Tosoh Corporation), an adduct-type polyisocyanate compound, was used as the crosslinking agent.

[0087] Example 4 In the spunbond spinning of Example 1, the single hole discharge rate was 0.25 g / min, and the ejector was fed with 0.75 kg / cm 2 A long-fiber fleece was obtained under the same conditions, except that dry air was supplied at a pressure (jet pressure) of 1000 g / m. The fiber diameter of the obtained long-fiber fleece was 12.5 μm, the birefringence Δn was 0.018, and the converted spinning speed was 1480 m / min. A nonwoven fabric was obtained from the obtained long-fiber fleece in the same manner as in Example 1. The basis weight of the nonwoven fabric was 220 g / m. 2 The thickness was 650 μm. A molding sheet was obtained in the same manner as in Example 3, except that the nonwoven fabric was used.

[0088] Example 5 In the spunbond spinning of Example 1, the single hole discharge rate was 0.52 g / min, and the ejector was fed with 0.75 kg / cm 2A long-fiber fleece was obtained under the same conditions, except that dry air was supplied at a pressure (jet pressure) of 1000 g / m. The fiber diameter of the obtained long-fiber fleece was 17 μm, the birefringence Δn was 0.018, and the converted spinning speed was 1650 m / min. A nonwoven fabric was obtained from the obtained long-fiber fleece in the same manner as in Example 1. The basis weight of the nonwoven fabric was 220 g / m. 2 The thickness was 650 μm. A molding sheet was obtained in the same manner as in Example 3, except that the nonwoven fabric was used.

[0089] Example 6 A molding sheet was obtained in the same manner as in Example 3, except that Vylon 670 (manufactured by Toyobo Co., Ltd.) was used as resin A.

[0090] Example 7 A molding sheet was obtained in the same manner as in Example 3, except that the resin layer coating material was applied to the release film at a rate of 250 g per square meter.

[0091] Example 8 A molding sheet was obtained in the same manner as in Example 3, except that the resin layer coating material was applied to the release film at a rate of 450 g per square meter.

[0092] Example 9 A molding sheet was obtained in the same manner as in Example 3, except that the resin layer coating material was applied to the release film at a rate of 600 g per square meter.

[0093] Examples 10 to 12 A molding sheet was obtained in the same manner as in Examples 7 to 9, except that 10 parts by mass of soft magnetic flat powder (FME3D-AH) having an average particle size of 50 μm manufactured by Sanyo Special Steel Co., Ltd. was added to the resin layer coating material while stirring.

[0094] Examples 13 to 15 A molding sheet was obtained in the same manner as in Examples 7 to 9, except that 30 parts by mass of soft magnetic flat powder (FME3D-AH) having an average particle size of 50 μm manufactured by Sanyo Special Steel Co., Ltd. was added to the resin layer coating material while stirring.

[0095] Comparative Example 1 A laminate with a release film was obtained in the same manner as in Example 1, except that a polyester spunbond nonwoven fabric (Ekure (registered trademark) W6B61A) manufactured by Toyobo Co., Ltd. was used as the nonwoven fabric, and after leaving it in a room heated to 60°C for 48 hours, the release film was peeled off to obtain a molding sheet. The basis weight of the nonwoven fabric was 210 g / m 2 , and the thickness was 650 μm.

[0096] Comparative Example 2 The following resin and solvent were mixed in the following ratio, heated to 30° C., and dissolved in a stirrer, and a crosslinking agent was added in the following ratio to obtain a coating material for the resin layer. Resin: 100 parts of acrylic resin (commercially available) with a number average molecular weight of 180,000 Solvent: 150 parts methyl ethyl ketone Dimethylformamide 50 parts Crosslinking agent: Blocked isocyanate 7960 (Baxenden) 8 parts

[0097] Next, using the same spunbond nonwoven fabric as in Example 1, a laminate with a release film was obtained in the same manner as in Example 1, and after leaving it in a room heated to 60°C for 48 hours, the release film was peeled off to obtain a molding sheet.

[0098] Comparative Example 3 A molding sheet was obtained in the same manner as in Example 3, except that Vylon 200 (manufactured by Toyobo Co., Ltd.) was used as the resin for the resin layer and the temperature during transfer of the resin layer was 70°C.

[0099] Comparative Example 4 A molding sheet was obtained in the same manner as in Example 3, except that Vylon GK-880 (manufactured by Toyobo Co., Ltd.) was used as the resin for the resin layer and the temperature during transfer of the resin layer was 90°C.

[0100] Evaluations were carried out using the molding sheets of Examples 1 to 15 and Comparative Examples 1 to 4. The results are shown in Tables 1 and 2.

[0101] [Table 1]

[0102] [Table 2]

[0103] In Tables 1 and 2, A is an adduct type isocyanate compound (Coronate HL), B is a block biuret type polyisocyanate compound (7960), and C is an isocyanurate type polyisocyanate compound (Coronate HX).

[0104] As shown by the above results, the molding sheets of Examples 1 to 15 could be molded in a drawing process with a push-in depth of 20 mm or less without causing any visually noticeable damage to the spunbond nonwoven fabric and resin layer.

[0105] On the other hand, the molding sheet of Comparative Example 1 had a birefringence Δn of the fibers of the spunbond nonwoven fabric outside the range of 0.005 or more and 0.050 or less, and visually noticeable tears occurred in the spunbond nonwoven fabric during squeezing with a push-in depth of 20 mm.

[0106] The molding sheet of Comparative Example 2 had a number average molecular weight of the resin in the resin layer that exceeded the range of 5,000 or more and 150,000 or less, and when squeezed with a push-in depth of 20 mm, the resin layer peeled off and visually noticeable tears occurred in the resin layer.

[0107] The molding sheets of Comparative Examples 3 and 4 exceeded the glass transition temperature (Tg) of the resin of the resin layer, which was 35° C. or less, and visually noticeable tears occurred in the resin layer during drawing with a push-in depth of 20 mm. [Explanation of symbols]

[0108] 1. Nonwoven fabric 1s Non-woven surface 2 Resin layer 3 Impregnation part 3s Impregnated surface of impregnated part 4 Non-impregnated area 4s Surface of non-impregnated part 10 Molded Sheet

Claims

1. A nonwoven fabric and a resin layer laminated on the nonwoven fabric, The nonwoven fabric contains fibers having a birefringence Δn of 0.005 or more and 0.050 or less, and the content of the fibers in 100% by mass of the nonwoven fabric is 90% by mass or more, The nonwoven fabric contains, relative to 100 mass% of fibers contained in the nonwoven fabric, a polyester resin having an intrinsic viscosity of 0.3 dl / g or more and 0.9 dl / g or less in an amount of 92 mass% or more and 99.8 mass% or less, and a high Tg organic compound having a glass transition temperature higher than that of the polyester resin in an amount of 0.02 mass% or more and 8 mass% or less, The resin layer contains a resin A having a number average molecular weight of 5,000 or more and 150,000 or less and a glass transition temperature (Tg) of 35° C. or less, The content of the resin A in 100% by mass of the resin layer is 90% by mass or more, and the resin A is a polyester resin, The molding sheet, wherein the resin layer comprises an impregnated portion in which the nonwoven fabric is impregnated and a non-impregnated portion in which the nonwoven fabric is not impregnated.

2. The molding sheet according to claim 1 , wherein the resin layer contains a metal filler.

3. The molding sheet according to claim 1 or 2, wherein the resin layer contains a crosslinking agent.

4. 4. The molding sheet according to claim 1, wherein the average thickness of the non-impregnated portion is smaller than the average thickness of the nonwoven fabric.

5. 5. The molding sheet according to claim 1, wherein the average thickness of the non-impregnated portions is greater than the average thickness of the impregnated portions.

6. A molded product obtained by molding the molding sheet according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Manufacture of honeycomb structure and adhesive sheet used for said manufacture

    JP1988111044A

  • Waterproof decorative sheet, its production, and waterproof decorative sheet composite panel

    JP1994115018A

  • Nonwoven fabric synthesis structure and its manufacture

    JP1997169082A

  • Laminated nonwoven fabric, its manufacture, thermal stencil base sheet and its manufacture

    JP2000238156A

  • Molding cushioning material and method for manufacturing laminated sheet

    JP2003191267A